Factors Associated with Help Seeking Behavior of Turkish Women with Urinary Incontinence; A Single Center Cross-Sectional Study - Seyhan Sönmez; Ersen Eraydın; Yalçın Arıcan; Ferhan Sönmez (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objectives: The aim of this study was to determine the patient and UI-related factors affecting help seeking behavior of Turkish women with undiagnosed urinary incontinence